Removal of diclofenac sodium from aqueous solution by Isabel grape bagasse - Antunes, Márjore (2019)
The aim of the present work was to evaluate the morphologic and chemical characteristics of Isabel grape (Vitis labrusca × Vitis vinifera) bagasse and to describe the adsorption of diclofenac sodium (DCF) from aqueous solutions by this biomass. Grape bagasse constituted mainly of particles with heterogeneous shapes and sizes, and it exhibited a macroporous structure and a low specific surface area (∼2 m2 g−1). The adsorbent material was also rich in oxygenated functional groups, especially –OH, and required an acidic pH to neutralize its surface. With respect to the adsorption of DCF, the percentage removal did not appear to depend on the initial concentration of the pharmaceutical. A pseudo-second-order kinetic model described the rate-controlling step, and the adsorption isotherms were well fitted by the Freundlich model. Concerning the thermodynamic data, the results showed that the adsorption of DCF onto grape bagasse occurred via an exothermic process accompanied by a decrease in the randomness at the solid/solution interface. Furthermore, the removal percentages of DCF ranged from 16.4% to 22.8%.